Study of Sports Analytics in Making Strategies in Sports: A Meta-Analysis - Dr. Bharatkumar Chaudhari; MS. Dharti Savani (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This case study was an exploration of how players, sport coaches and teachers use analysis to improve performance and making strategies in any sports. The study helped to reveal the usage of performance analysis and its perceived advantages and barriers. The study helped to determine frameworks for practical use by professional players and coaches. Data revealed a lack of use due to the lack of understanding of how to use performance analysis to improve sports performance as well as making strategies in sports. Professional development remains a high need in education and the study revealed self performance analysis as a viable option as a professional players and coaches. In this study the need for training on how to utilize performance analysis and frameworks put into place for players and instructional coaches.
Keywords: performance; sports analysis; making strategies; sports